Late Outcome of Direct Vision Urethrotomy in Patients with Urethral Stricture at Kilimanjaro Christian Medical Center (KCMC), Moshi-Tanzania (Global Journal of Medical Research, 2015)
Abstract not found
Keywords: urethral stricture; outcome